Social Structure of Accumulation Theory, Marxist Theory, and System Transformation - Kotz, David M. (The Review of radical political economics, 2017)
This paper locates social structure of accumulation (SSA) theory in relation to traditional Marxism. It then applies SSA theory to analyze the current trajectory of system transformation in the global system. Drawing lessons from the global crisis of the 1930s, it uses SSA theory to illuminate the causes and possible consequences of the system transformation that now appears to be developing—a transformation that may be replacing parliamentary democracies by right-wing nationalist repressive regimes in many countries.